Kingdom of Lesotho : Country Partnership Framework 2016-2020 - World Bank Group (World Bank, Washington, DC, 2016)
Lesotho is one of the poorest countries in Southern Africa, and has one of the highest income inequality in the world. Home to about 2 million people, Lesotho is surrounded by South Africa, the second largest and most industrialized economy in Africa. Lesotho generates income mainly by exporting textiles, water, and diamonds, and is a member of the Southern African Customs Union (SACU), the Southern African Development Community (SADC), and the Common Monetary Area (CMA). The national currency, the loti, is pegged to the South African rand. Lesotho's main trading partners are South Africa and the United States. The CPF will seek to mitigate four substantial risks to the implementation of the WBG program: (a) political and governance; (b) macroeconomic; (c) climate change and climate- induced disasters; and (d) operating risks (capacity and fiduciary). The lessons from the Country Assistance Strategy Completion and Learning Report (CPS CLR) will play an important role in addressing these risks. The CPF will give high importance to quality and risks at entry for new operations, and continue strong monitoring and supervision. These mitigation factors are essential for achieving sustainable results.